EDUKASI MEDIA SOSIAL YANG CEPAT, KREATIF, DAN AMAN MELALUI DIGITAL TREASURE HUNT DI MADRASAH ALIYAH BINA INSANI - Novita Lestari Anggreini; Nia Ekawati (PUAN INDONESIA, 2026)
Research by Effendy and Oktiani (2024) shows that cybersecurity literacy is crucial for adolescents in dealing with online manipulation. Based on this urgency, the community service team held an interactive counseling session themed " Fast, Creative, and Safe Social Media Education Through a Digital Treasure Hunt at Madrasah Aliyah Bina Insani "The activity took place on Thursday, January 22, 2026, in the classroom of MA Bina Insani. This seminar-style counseling was attended by 28 students who actively participated through discussions and question-and-answer sessions. As a token of appreciation, the team also presented a certificate of commendation as a souvenir. Field evaluations indicated that the school felt greatly assisted by the program. Through this activity, students began to understand digital threats such as cyberbullying and fake news. The Principal, Mr. Samsudin, S.Pd.I., welcomed and fully supported this program so that students could become more responsible in using social media.